A nonlinear damage constitutive model of PVC coated fabrics. (April 2021) - Lanlan, Zhang; Yingying, Zhang; Wei, Song; Junhao, Xu; Jigang, Xue
Abstract: A simple and effective damage constitutive model for PVC-coated fabrics be developed, which could be used to predict the nonlinear mechanical response of membrane structures under tension more accurately. In this paper, based on continuum damage mechanics theory, a nonlinear damage constitutive model for PVC-coated fabrics was established. Firstly, the off-axis tensile tests were carried out on the membrane material at 0 °, 15 °, 30 °, 45 °, 60 °, 75 °, and 90 ° with an electronic universal tensile testing machine, and the tensile curves of seven specimens were obtained. Then, the Helmholtz free energy function is constructed based on the continuum damage mechanics theory and the existing research foundation, and the constitutive equation of the material is derived. Then, according to the characteristics of the off-axial tensile test curve of the coated fabrics, a damage evolution equation for the materials under tension was established with strain as an independent variable. By compiling a MATLAB program of the constitutive model, the parameters were obtained, and the off-axial tensile test curves of PVC-coated fabrics were predicted. The constitutive model was compiled using the user-defined subroutine UMAT in ABAQUS, and the correctness of the model was verified by simulating a static loading test of the membrane structure under in-plane tension. The model shows a good performance in computation and the obtained results are also in good agreement with experimental data. These features enable the proposed model to be used in numerical calculations for membrane structures.